Extracellular matrix at the muscle – tendon interface: functional roles, techniques to explore and implications for regenerative medicine. (2nd January 2021) - Narayanan, Naagarajan; Calve, Sarah
ABSTRACT: The muscle-tendon interface is an anatomically specialized region that is involved in the efficient transmission of force from muscle to tendon. Due to constant exposure to loading, the interface is susceptible to injury. Current treatment methods do not meet the socioeconomic demands of reduced recovery time without compromising the risk of reinjury, requiring the need for developing alternative strategies. The extracellular matrix (ECM) present in muscle, tendon, and at the interface of these tissues consists of unique molecules that play significant roles in homeostasis and repair. Better, understanding the function of the ECM during development, injury, and aging has the potential to unearth critical missing information that is essential for accelerating the repair at the muscle-tendon interface. Recently, advanced techniques have emerged to explore the ECM for identifying specific roles in musculoskeletal biology. Simultaneously, there is a tremendous increase in the scope for regenerative medicine strategies to address the current clinical deficiencies. Advancements in ECM research can be coupled with the latest regenerative medicine techniques to develop next generation therapies that harness ECM for treating defects at the muscle-tendon interface. The current work provides a comprehensive review on the role of muscle and tendon ECM to provide insights about the role of ECM in the muscle-tendon interface and discusses the latest research techniques to explore the ECM to gathered information for developing regenerative medicine strategies.